Prinsip Keabadian Manfaat dalam Hukum Wakaf: Telaah Filosofis dan Implikasinya bagi Pemberdayaan Umat - Ramzy Ilya Dzimar; Achmad Rafli Weking; Fikri Erlangga; Sawitri Yuli Hartati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The principle of perpetuity of benefit in waqf law represents a fundamental concept that connects religious devotion with sustainable social welfare. Waqf is not merely the act of transferring assets, but a long-term commitment to ensuring continuous benefits for society across generations. This study examines the philosophical foundations of the perpetuity of benefit in Islamic law and analyzes its legal formulation within the Indonesian waqf regulatory framework. Using a normative juridical and philosophical approach, the research highlights how Islamic legal principles, national legislation, and institutional practices interact in preserving the sustainability of waqf benefits. The findings indicate that the realization of perpetual benefit depends on professional waqf management, strong institutional support, effective supervision, and adaptive utilization of productive waqf instruments. Moreover, innovation in waqf management, including cash waqf and digital waqf, must remain aligned with sharia objectives and legal certainty. Ultimately, strengthening the principle of perpetuity of benefit positions waqf as a strategic instrument for empowering communities and supporting sustainable socio-economic development.